2019
DOI: 10.1002/ijc.32267
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of single nucleotide polymorphisms identified in genome‐wide association studies determine risk for colorectal cancer

Abstract: Genome‐wide association studies (GWASs) have identified single nucleotide polymorphisms (SNPs) associated with colorectal cancer (CRC) risk, but whether these SNPs have additive effects on the risk of CRC remains unclear. We performed a systematic analysis of GWAS‐identified SNPs using GWAS datasets from China (2,248 patients and 3,173 controls) and Europe (4,461 patients and 4,140 controls). We analyzed 58 independent variants from DNA samples from Chinese populations and found 19 SNPs that were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“… Model were compared among each other respect to NRI (95%CI; p -value) and IDI (95%CI; p -value): the simple-count-GRS vs. logistic regression weighted OR-GRS showed an NRI of − 0.082 (− 0.159, − 0.007; p value: 0.033) and an IDI of − 0.002 (− 0.004, − 2.33E− 04; 0.028); the simple-count-GRS vs. explained variance weighted OR-GRS showed an NRI of 0.017 (− 0.055, 0.090; 0.638) and an IDI of 2.80E− 04 (− 0.001, 0.001; 0.567); logistic regression weighted-GRS vs. explained variance weighted OR-GRS showed an NRI − 0.077 (− 0.153, − 0.001; 0.046) and an IDI of − 5.54E− 04 (− 0.001, − 3.17E− 05; 0.038). In addition, a model including only smoking factors was with a model including smoking factors and simple count GRS (SC-GRS), with an increased AUC, NRI and IDI in combined model of 0.084, 0.317 (0.225, 0.408) and 0.031 (0.023, 0.039) Xin J, 2019 [ 52 ] Case-control Chinese Chinese studies: 2248 cases and 3173 controls; GECCO study: 4461 cases and 4140 controls Chinese studies: 19 SNPs vs. 58 SNPs; GECCO study: 19 SNPs vs. 75 SNPs Weighted GRS using weights derived from the same study Gender, age, first principal component Chinese studies: 19 SNPs model of 0.597 (0.581–0.613), 58 SNPs model of 0.623 (0.604–0.642); GECCO study: 19 SNPs model of 0.575 (0.563–0.587), 58 SNPs model of 0.585 (0.573–0.597) Yeh CC, 2007 [ 53 ] Case-control Taiwanese 727 cases and 736 controls 10 SNPs Age, education, physical activity, coffee consumption, cigarette consumption, alcohol use, staple consumption, meat, vegetable/fruit and fish/shrimp intake. Zhang L, 2017 [ 54 ] Case-control Chinese 369 cases and 929 controls 4 SNPs Age, BMI, physical activity, emotion status, mental stress, cholesterol, drinking and smoking, vegetables and seafood consumption CRC colorectal cancer, SNP single nucleotide polymorphism, ERS environmental risk score, GRS genetic risk score, TRS traditional risk score, PRS polygenic risk score, ct-DNA circulating tumor-DNA, RR relative risk, HR hazard ratio, OR odds ratio, GWAS genome-wide association study, BMI body mass index, FH family history, NSAID nonsteroidal anti-inflammatory drug …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Model were compared among each other respect to NRI (95%CI; p -value) and IDI (95%CI; p -value): the simple-count-GRS vs. logistic regression weighted OR-GRS showed an NRI of − 0.082 (− 0.159, − 0.007; p value: 0.033) and an IDI of − 0.002 (− 0.004, − 2.33E− 04; 0.028); the simple-count-GRS vs. explained variance weighted OR-GRS showed an NRI of 0.017 (− 0.055, 0.090; 0.638) and an IDI of 2.80E− 04 (− 0.001, 0.001; 0.567); logistic regression weighted-GRS vs. explained variance weighted OR-GRS showed an NRI − 0.077 (− 0.153, − 0.001; 0.046) and an IDI of − 5.54E− 04 (− 0.001, − 3.17E− 05; 0.038). In addition, a model including only smoking factors was with a model including smoking factors and simple count GRS (SC-GRS), with an increased AUC, NRI and IDI in combined model of 0.084, 0.317 (0.225, 0.408) and 0.031 (0.023, 0.039) Xin J, 2019 [ 52 ] Case-control Chinese Chinese studies: 2248 cases and 3173 controls; GECCO study: 4461 cases and 4140 controls Chinese studies: 19 SNPs vs. 58 SNPs; GECCO study: 19 SNPs vs. 75 SNPs Weighted GRS using weights derived from the same study Gender, age, first principal component Chinese studies: 19 SNPs model of 0.597 (0.581–0.613), 58 SNPs model of 0.623 (0.604–0.642); GECCO study: 19 SNPs model of 0.575 (0.563–0.587), 58 SNPs model of 0.585 (0.573–0.597) Yeh CC, 2007 [ 53 ] Case-control Taiwanese 727 cases and 736 controls 10 SNPs Age, education, physical activity, coffee consumption, cigarette consumption, alcohol use, staple consumption, meat, vegetable/fruit and fish/shrimp intake. Zhang L, 2017 [ 54 ] Case-control Chinese 369 cases and 929 controls 4 SNPs Age, BMI, physical activity, emotion status, mental stress, cholesterol, drinking and smoking, vegetables and seafood consumption CRC colorectal cancer, SNP single nucleotide polymorphism, ERS environmental risk score, GRS genetic risk score, TRS traditional risk score, PRS polygenic risk score, ct-DNA circulating tumor-DNA, RR relative risk, HR hazard ratio, OR odds ratio, GWAS genome-wide association study, BMI body mass index, FH family history, NSAID nonsteroidal anti-inflammatory drug …”
Section: Resultsmentioning
confidence: 99%
“…In order to include genetic factors into prediction models, different methodologies were investigated across the included studies. In particular, 26 (78.79%) studies used a GRS, 11 (42.31%) of which used a weighted GRS [ 31 , 33 35 , 40 , 42 46 , 52 ], other 6 (23.08%) studies used an unweighted GRS [ 22 , 24 , 26 29 ]. Instead, a total of 9 studies (34.62%) used both unweighted and weighted methods to develop risk scores [ 23 , 25 , 30 , 32 , 36 , 37 , 49 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence demonstrated that ion channel genes contribute to the progression of various carcinomas, and the proliferation of several cell types. 3540 We explored the correlation between rs3331, rs1051295, and rs11468831 variants and the response to chemotherapy among CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The genotyping data of GWAS of colorectal cancer and LC were derived from previous studies. 45,46 DAK is available from Github: https://github.com/fbaothu/DAK. Other tools used in this work can be downloaded from: Plink: http://zzz.bwh.harvard.edu/plink/; HAPGEN 2: https://mathgen.stats.…”
Section: Data and Code Availabilitymentioning
confidence: 99%